Symbolic Violence on Characters in "Ocean's 8" Movie by Gary Ross: Susilawati, Rahmawati Azi, Nur Israfyan Sofian - Susilawati tila risma (ELITE: Journal of English Language and Literature, 2016)
This study discusses symbolic violence in Ocean’s 8 movie. Ocean's 8 is an American heist comedy movie directed by Gary Ross and produced by Warner Bros  Picture 2018.  This study is aimed to analyze the issue of symbolic violence which is usually carried out by the dominant person (superior) to dominate people who don’t have power. This study is related to Pierre Bourdieu’s theory called symbolic violence. The method of this is descriptive qualitative. The data were collected through the process of watching, pausing, screen-shooting and note-taking, and classifying, and then the writer analyzed those data by using the theory of symbolic violence by Pierre Bourdieu. The results of the study show that symbolic violence is influenced by the presence of habitus and adequate capital to form the dominant habitus and symbolic power that produces symbolic violence. The forms of symbolic violence in this movie consist of euphemisms and sensory mechanisms are gift-giving, giving motivation and support, utilizing weaknesses owned by a person, and utilizing the position as a leader. All these forms of symbolic violence are carried out by the main character, Debbie as the team leader in the mission.